Genetic analysis of insulin-like growth factor II and HLA-G in pre-eclampsia. (February 2000) - Bermingham, J.; Jenkins, D.; McCarthy, T.; O'Brien, M.
Abstract : Pre-eclampsia (PE) is uniquely a disease of pregnancy and is the major cause of foetal and maternal morbidity and mortality. Epidemiological studies show that PE is highly heritable, with a high incidence in all populations. The underlying pathology indicates that absent or shallow invasion of foetal trophoblasts into maternal arteries is a feature of true PE. The objective of this study was to determine the genetic factors influencing PE. A large number of mother-father-baby trios were collected in which the first pregnancy was complicated by severe PE. After careful examination of the epidemiology and pathology of the disease, two plausible candidate genes, namely insulin-like growth factor II (IGF-II) and HLA-G, were analysed for association with PE. No association was found between a commonly occurring polymorphism in IGF-II and PE. Three polymorphisms in HLA-G were analysed in the sample cohorts. No association was found between three polymorphisms in HLA-G and PE. However, the frequency of the HLA-G insertion/deletion polymorphism in exon 8 deviated significantly from Hardy-Weinberg expectations in PE off-spring, reflecting an excess of heterozygotes for these polymorphisms in PE offspring. The significance of this deviation is not clear and further genetic analysis will be necessary to confirm this finding and to explore further the candidacy of HLA-G in PE.